Implementasi Nilai-Nilai Kitab Ta’lim Muta’allim Dalam Pembentukan Karakter Santri Dipondok Pesantren Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Aminah Desfitria; Ratika Novianti; Halimatus Sa’diyah (Journal on Education, 2024)
This study aims to analyze: (1) Implementation of the values ​​in the Ta'lim Al-Muta'allim Book in the Formation of the Character of Students at the Hidayatul Mubtadiin Islamic Boarding School, Sidoharjo, Jati Agung, South Lampung. (2) What are the obstacles faced and solutions in the implementation of the values ​​in the Ta'lim Al-Muta'allim Book in the Formation of the Character of Students at the Hidayatul Mubtadiin Islamic Boarding School, Sidoharjo, Jati Agung, South Lampung. This type of research uses a qualitative descriptive approach. The location of the research is at the Hidayatul Mubtadiin Islamic Boarding School, Sidoharjo, Jati Agung, South Lampung as a source of data to obtain a portrait of the values ​​of the Ta'lim Muta'allim Book. The data was obtained using observation, interview and documentation methods. All data were analyzed interactively and continuously, including data reduction, presentation, and verification. The results of this study indicate that: (1) The implementation of the values ​​of the Ta'lim Al-Muta'allim book at the Hidayatul Mubtadiin Islamic Boarding School in Sidoharjo Jati Agung, South Lampung is carried out with a system of reading the book, interpreting the gandul, memorizing the nadhoman from the book. Especially the Ta'lim Al-Muta'allim moral book is related to the morals of students, so from this learning students are required to read and understand after that they are also required to apply examples of good attitudes contained in the Ta'lim Al-Muta'allim book. The relationship between character formation is from the material taught regarding several morals in the material, students are required to behave politely after there is direction related to the material that has been taught or has not been delivered, so that a noble soul is embedded. (2) The obstacles faced and solutions in implementing the values ​​of the Ta'lim Al-Muta'allim book in the formation of the character of students at the Hidayatul Mubtadiin Islamic Boarding School, Sidoharjo, Jati Agung, South Lampung, namely that there are still many students who have not been able to master Javanese. The solution to the obstacles faced is that the Ustadz in his delivery uses two languages, namely using Javanese and then explained with information using Indonesian, in order to continue to exist and maintain the knowledge of the Salaf